Vicki Stroeher, Nicholas Clark and Jude Brimmer (eds), My Beloved Man: The Letters of Benjamin Britten and Peter Pears (2016) - Saylor, Eric (Journal of the Society for Musicology in Ireland, 2017)
A review of Vicki Stroeher, Nicholas Clark and Jude Brimmer (eds), My Beloved Man: The Letters of Benjamin Britten and Peter Pears, Aldeburgh Studies in Music, 10 (Woodbridge: The Boydell Press, 2016). ISBN 978-1-783-27108-5.